Inhibitorty Activity of Lemongrass (Cymbopogon Nardus, (L.) Rendle) Essential Oils on The Growth of Bacterial Phorpyromonas Gingivalis and Aggregatibacter Actinomycetemcomitans In Vitro - Suprianto, Kosno; Emriadi, Emriadi; Kodir, Ade Ismail Abdul; Lestari, Dian (Odonto : Dental Journal, 2024)
Background: Periodontal disease is one of oral and dental health problems that suffered by many people in the world and occurs in 50% of adult population. Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are the main bacteria that cause periodontitis. One of the plants that is often used as an alternative antimicrobial agent is citronella (Cymbopogon nardus L.) which contains citronellal and geraniol compounds. This study aims to determine whether the essential oils of lemongrass leaves have inhibitory effect on the growth of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in vitro. Method: The production of lemongrass essential oils is carried out by the distillation method and 25%, 50%, and 75% concentration of essential oils are diluted using Tween 20 and distilled water. The inhibition test was carried out by the Kirby-Bauer disk diffusion method on Mueller Hinton Agar media. Result: The analysis showed that there was a significant difference between the inhibitory power produced by each concentration of essential oil of citronella leaf on the growth of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans. Conclusion: The conclusion of this study is the essential oils of lemon grass with concentrations of 25%, 50%, 75%, and 100% have different inhibitory properties in inhibiting the growth of Porphyromonas gingivalis bacteria and Aggregatibacter actinomycetemcomitans.